Relationship between Human Resources and Authority Implementation of Health Operational Assistance (BOK) at Padangsidimpuan Health Center in 2018 - Muhammad Abdullah Nasution; Destanul Aulia; Juanita Juanita (Budapest International Research and Critics University, 2020)
BOK (Health Operational Aid) is the aid policy from the central government to local governments for special public health at Puskesmas. Padangsidimpuan is the BOK acceptor with receiving fund below the target: 76.85% in 2017 and 87.30% in 2018. The objective of the research was to analyze human resources and authority which were correlated with the implementation of BOK at Puskesmas of Padangsidimpuan. The research used mixed methods with concurrent embedded. The population was 30 people consisted of the Head of Puskesmas, those in charge of public health, and the officials of BOK, and all of them were used as the samples. The data were gathered by conducting interviews and questionnaires and analyzed by using Rank Spearman analysis at α=0.05. The result of the research showed that human resources and authority were in moderate category (53.3%). The factor of resources had the most dominant related (p=0,001). It is recommended that the management of Puskesmas and the Health Agency of Padangsidimpuan increase the quality of resources, equal distribution, and professionalism. The health care providers should carry out the policy of BOK in order to increase public health standard.